2018
DOI: 10.1021/acs.inorgchem.8b00517
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Oxidation of Fine UO2 Powders: Thermochemistry and Kinetics

Abstract: The thermochemical behavior of low-temperature oxidation in fine UO powders has been investigated by simultaneous thermogravimetric analysis and differential scanning calorimetry. The evaluation of the thermochemical and kinetic data reveals a complex interplay between different mechanisms. The initial reaction concerns the rapid chemisorption of oxygen gas onto the surface of UO grains, having an activation energy of only 13.1 ± 0.6 kJ mol. The subsequent oxidation at temperatures between 40 and 100 °C occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…A simultaneous thermal analyzer (Netzsch STA 449 F1 Jupiter) was used for synthesis of the more delicate sample materials such as UO 2.0 and β-UO 3 . To lower the susceptibility toward unwanted oxidation, 30 the reduction treatment on the UO 2 powder was repeated at a higher temperature of 900 °C, which results also in a decrease of the specific surface area. After being cooled to room temperature, the STA was flushed first with pure Ar, and then with Ar containing about 80 ppm of O 2 to gently expose the powder to mildly oxidizing conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A simultaneous thermal analyzer (Netzsch STA 449 F1 Jupiter) was used for synthesis of the more delicate sample materials such as UO 2.0 and β-UO 3 . To lower the susceptibility toward unwanted oxidation, 30 the reduction treatment on the UO 2 powder was repeated at a higher temperature of 900 °C, which results also in a decrease of the specific surface area. After being cooled to room temperature, the STA was flushed first with pure Ar, and then with Ar containing about 80 ppm of O 2 to gently expose the powder to mildly oxidizing conditions.…”
Section: Methodsmentioning
confidence: 99%
“…9 Upon further oxidation in the low-temperature region, morphotropic phase transformations take place with formation of mixed-valence compounds, commonly referred to as U4O9, U3O7, and U3O8. [12][13][14][15] The oxides U4O9 and U3O7 are structurally closely related to the original fluorite-type crystal lattice, while the transformation to U3O8 induces a more drastic crystallographic reorganization which is associated with a considerable volume increase (36 vol.%).…”
Section: Introductionmentioning
confidence: 99%
“…At temperatures above 700 K, a wide nonstoichiometric solid solution phase field (UO 2+ x ) gradually develops, but at lower temperatures only slight deviations from stoichiometry (0 < x < 0.03) can occur . Upon further oxidation in the low-temperature region, morphotropic phase transformations take place with formation of mixed-valence compounds, commonly referred to as U 4 O 9 , U 3 O 7 , and U 3 O 8 . The oxides U 4 O 9 and U 3 O 7 are structurally closely related to the original fluorite-type crystal lattice, while the transformation to U 3 O 8 induces a more drastic crystallographic reorganization, which is associated with a considerable volume increase (36 vol %).…”
Section: Introductionmentioning
confidence: 99%
“…23−25 Studies performed on powders showed that particles under a certain size (200 nm) did not develop U 3 O 8 while being oxidized under air. 26,27 Similar oxidation studies were performed also on sintered UO 2 pellets, 19 but never focused on the impact of the grain size on the oxidation behavior. As the grain size characteristic of the HBS also falls below the critical thickness of the U 3 O 7 for cracking (0.4 μm), 19 this work aims to investigate potential differences in the oxidation behavior of HBS with respect to the bulk of the fuel.…”
Section: Introductionmentioning
confidence: 99%